Implikasi Adopsi IFRS Sustainability Standards terhadap Peningkatan Non-Audit Fees dan Independensi Auditor: Studi Kualitatif pada KAP di Indonesia - Ary Haritsaning Atmadya; Dirgahayu Almi Mahati; Anak Agung Gde Satia Utama (Owner : Riset dan Jurnal Akuntansi, 2026)
The issuance of IFRS S1 General Requirements for Disclosure of Sustainability-related Financial Information and IFRS S2 Climate-related Disclosures by the International Sustainability Standards Board (ISSB) has fundamentally transformed the landscape of sustainability reporting, shifting it from a voluntary regime toward a framework integrated with general-purpose financial reporting. This transformation has driven a surge in demand for sustainability-related services, including IFRS S1/S2 implementation consulting and sustainability assurance, which are largely classified as non-audit services and have the potential to increase sustainability-related non-audit fees within the revenue structure of Public Accounting Firms (PAFs). This study adopts an interpretive qualitative approach based on literature review and document analysis (including standards, codes of ethics, research reports, and scholarly articles) to identify and categorize auditor independence threats—namely self-interest, self-review, advocacy, familiarity, and management participation—arising from the expansion of sustainability services following IFRS S1/S2. The findings indicate that the joint provision of IFRS S1/S2 consulting and assurance services by the same audit firm may strengthen economic dependence, create self-review and advocacy threats, and blur the boundary between the roles of consultant and independent auditor. On the other hand, the profession and regulators have begun to respond by strengthening safeguards, such as restricting the types of services provided, implementing fee caps, separating advisory and assurance teams, and reinforcing ethical frameworks for sustainability assurance.